Aortic 4D flow MRI in 2 minutes using compressed sensing, respiratory controlled adaptive k‐space reordering, and inline reconstruction. Issue 6 (25th February 2019) - Ma, Liliana E.; Markl, Michael; Chow, Kelvin; Huh, Hyungkyu; Forman, Christoph; Vali, Alireza; Greiser, Andreas; Carr, James; Schnell, Susanne; Barker, Alex J.; Jin, Ning
Abstract : Purpose: To evaluate the accuracy and feasibility of a free‐breathing 4D flow technique using compressed sensing (CS), where 4D flow imaging of the thoracic aorta is performed in 2 min with inline image reconstruction on the MRI scanner in less than 5 min. Methods: The 10 in vitro 4D flow MRI scans were performed with different acceleration rates on a pulsatile flow phantom (9 CS acceleration factors [R = 5.4–14.1], 1 generalized autocalibrating partially parallel acquisition [GRAPPA] R = 2). Based on in vitro results, CS‐accelerated 4D flow of the thoracic aorta was acquired in 20 healthy volunteers (38.3 ± 15.2 years old) and 11 patients with aortic disease (61.3 ± 15.1 years) with R = 7.7. A conventional 4D flow scan was acquired with matched spatial coverage and temporal resolution. Results: CS depicted similar hemodynamics to conventional 4D flow in vitro, and in vivo, with >70% reduction in scan time (volunteers: 1:52 ± 0:25 versus 7:25 ± 2:35 min). Net flow values were within 3.5% in healthy volunteers, and voxel‐by‐voxel comparison demonstrated good agreement. CS significantly underestimated peak velocities (vmax ) and peak flow (Qmax ) in both volunteers and patients ( volunteers : vmax, −16.2% to −9.4%, Qmax : −11.6% to −2.9%, patients : vmax, −11.2% to −4.0%; Qmax, −10.2% to −5.8%). Conclusion: Aortic 4D flow with CS is feasible in a two minute scan with less than 5 min for inline reconstruction. While net flow agreement was excellent, CS with R = 7.7 produced underestimation of Qmax and vmax ; however, these were generally within 13% of conventional 4D flow‐derived values. This approach allows 4D flow to be feasible in clinical practice for comprehensive assessment of hemodynamics.